Giardia lamblia y su incidencia en la diarrea aguda en niños menores de 5 años de la ciudadela barrio lindo cantón Babahoyo los Ríos primer semestre 2015 - Rivas Abad, Gabriel (2015)
Giardia lamblia, intestinalis or duodenalis is a flagealdo protozoan pathogen belonging to the order diplomonad parasitizing the digestive tract of humans and other mammals, causing a disease called giardiasis, giardiasis or lambliasis. Giardiasis is widespread worldwide, but particularly prevalent in Southeast and South Asia: in Central and West Africa and Latin. Giardia is a parasite infestation caused by Giardia lamblia, a fairly common parasite in children and in adults. This is not only relatively common infection, but it is easy to go unnoticed as usual have no symptoms or these are difficult to detect, even in this post explains how suspect this table in many cases. The parasite can enter the body through contaminated food or water but also can be spread directly from one child to another, when a child who suffers still going to kindergarten or school, which, moreover, is normal if not detected the frame to be free from the child who suffers any symptoms. It seems that there may be ease of infection in children with cystic fibrosis and Crohn's disease, so these children sometimes must conduct regular checks, within its regular reviews. Prevention is based on maintaining good hygienic and sanitary conditions, treat family and close contacts of children and countering potential sources of contagion once located.